Meiotic Recombination Defects and Premature Ovarian Insufficiency - Chengzi Huang; Chengzi Huang; Chengzi Huang; Chengzi Huang; Ting Guo; Ting Guo; Ting Guo; Ting Guo; Yingying Qin; Yingying Qin; Yingying Qin; Yingying Qin (Frontiers in Cell and Developmental Biology, 2021)
Premature ovarian insufficiency (POI) is the depletion of ovarian function before 40 years of age due to insufficient oocyte formation or accelerated follicle atresia. Approximately 1–5% of women below 40 years old are affected by POI. The etiology of POI is heterogeneous, including genetic disorders, autoimmune diseases, infection, iatrogenic factors, and environmental toxins. Genetic factors account for 20–25% of patients. However, more than half of the patients were idiopathic. With the widespread application of next-generation sequencing (NGS), the genetic spectrum of POI has been expanded, especially the latest identification in meiosis and DNA repair-related genes. During meiotic prophase I, the key processes include DNA double-strand break (DSB) formation and subsequent homologous recombination (HR), which are essential for chromosome segregation at the first meiotic division and genome diversity of oocytes. Many animal models with defective meiotic recombination present with meiotic arrest, DSB accumulation, and oocyte apoptosis, which are similar to human POI phenotype. In the article, based on different stages of meiotic recombination, including DSB formation, DSB end processing, single-strand invasion, intermediate processing, recombination, and resolution and essential proteins involved in synaptonemal complex (SC), cohesion complex, and fanconi anemia (FA) pathway, we reviewed the individual gene mutations identified in POI patients and the potential candidate genes for POI pathogenesis, which will shed new light on the genetic architecture of POI and facilitate risk prediction, ovarian protection, and early intervention for POI women.